Drinking frequency in wild lactating chimpanzees (Pan troglodytes schweinfurthii) and their offspring. Issue 6 (2nd March 2022) - Nelson, Rachel S.; Lonsdorf, Elizabeth V.; Terio, Karen A.; Wellens, Kaitlin R.; Lee, Sean M.; Murray, Carson M.
Abstract: Maintaining water balance is essential for organismal health, and lactating females must balance individual needs with milk production and offspring hydration. Primate milk is dilute and presumed to be the primary source for infant hydration for a considerable time period. Few studies have investigated the hydration burden that lactation may place on female primates. In this study, we investigated sources of variation in female and offspring drinking frequency among wild chimpanzees ( Pan troglodytes ). We hypothesized females would experience seasonal and lactation hydration burdens and adjust their drinking behavior to accommodate these, but this hydration burden would vary between females of different dominance ranks. We also predicted that parity would relate to maternal drinking frequency since primiparous females are still investing in their own growth. Finally, we predicted that offspring would drink more in the dry season and as they aged and lost milk as a water source, but that offspring of high‐ranking females would be buffered from these effects. Using 41 years of long‐term data on the behavior of mothers and offspring of Gombe National Park, we found that mothers drank more in the dry season, but there was no significant difference between mothers of different ranks during this period. Low‐ranking females drank significantly more than mid‐ and high‐ranking females during late lactation. Offspring also drank more in the dry season and as they aged, but there was no evidence of buffering for those with high‐ranking mothers. While chimpanzees in our study population drank infrequently, they do demonstrate noticeable shifts in drinking behavior that suggests seasonal and reproductive hydration burdens. Abstract : Model predicted maternal drink counts ± SE by dominance rank, lactation stage, and season. Highlights: Chimpanzee mothers and their offspring drank more water in the dry season, regardless of maternal dominance rank. Low‐ranking mothers drank significantly more than mid‐ and high‐ranking females during late lactation, when offspring are 3–4.5 years of age, but there was no evidence of this difference in offspring. The Gombe chimpanzees demonstrate noticeable shifts in drinking behavior that suggests seasonal and reproductive hydration burdens.